Accounting truth and its assurance in entities from the Republic of Moldova - Viorel TURCANU; Irina GOLOCIALOVA (Audit Financiar, 2016)

(untitled)
The multiple users will not be able to make correct decisions, unless the information provided by accounting is exact and transparent. Otherwise we cannot state that it communicates the accounting truth with regard to the activity of a company. The accounting truth is determined by several factors, like the accounting technique, the principles and the qualitative characteristics, the accounting normalization and the audit. The objective of the study is to provide a general analysis of these factors, as well as to investigate the manner in which these support the assurance of the accounting truth in the Republic of Moldova (RM) in the context of the IFRS concept of true and fair view, also relying on practical examples from the banking system. The results of the study show that the accounting truth in RM entities is ensured to a large extent, due to the positive impact of these factors. At the same time, there is still room for improvement in theoretical matters of accounting and financial reporting, as well as for the development of the accounting legal framework, with the purpose of expanding the financial analysis potential of the disclosed information. The situation of the banking system shows that, if no adequate attention is paid to the operative and strategic analysis of the financial position and results, including based on audit, economically destructive phenomena can take place, both at entity-level, and at country-level.